Measuring the Ombudsman's Partisanship: An Analysis of Maladministration Oversight and Its Impact on Public Justice In Gorontalo - Polinggapo, Jefri; Usman, Masjrul Janto; Biongan, Ahiar; Nuna, Muten; Tabo, Sarfan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The Ombudsman has an important role in creating public justice through supervision of public services, but the effectiveness of this supervision is still hampered by various factors such as limited human resources, lack of public understanding, and resistance from some public service providers. Strategic steps are needed to improve the quality of human resources, expand socialization regarding the role of the Ombudsman, and strengthen cooperation with related agencies so that supervision of maladministration can run better and have a positive impact on the quality of public services in Gorontalo Province. This article aims to analyze the extent to which the Ombudsman's bias in supervising maladministration in Gorontalo Province influences the creation of public justice. This study uses a qualitative descriptive approach with an analytical method. The results of the study show that: 1) supervision of maladministration by the Ombudsman of Gorontalo Province is still hampered by several factors that affect its effectiveness in creating public justice. The main obstacle found is the limited human resources with only 12 staff which reduces efficiency in handling reports and cases of maladministration. Therefore, increasing the number of human resources and increasing capacity through routine training is important to improve the performance of the Ombudsman; 2) the lack of public insight regarding the role of the Ombudsman in supervising public services requires more intensive socialization to increase public understanding and participation; 3) although most public service providers respond positively to the existence of the Ombudsman, there is still a less than supportive attitude from several parties regarding maladministration. Therefore, there needs to be better coordination with local governments and strengthening understanding regarding the independence and neutrality of the Ombudsman to increase accountability and transparency in public services.